The Phratry of the imaginary : African writers and the Latin-American model from the 1980s onwards - (:unkn) unknown (My University, 2016)
The renewal of sub-Saharan French-speaking writings in the 1980s results in a remarkable overtaking of the geographical, linguistic, cultural and identical traditional borders. So opening to the universal letters, many African writers turn to the Latin American universe which fascinates them for its space, topics, aesthetics, imaginary. It is this Latin American orientation of the African novel, the implementation of a relationship in the modes of expression and the representation of reality, that we call imaginary phratry. A phenomenon with multiple issues, the analysis of the imaginary phratry can reveal how, inspired by a common history and culture, the African and Latin American universe are literally brought closer in a fraternal posture reflecting some transatlantic solidarity.
Keywords: African Research